Analisis Bibliometrik Keyword Mapping” “Evolusi Konsep Problem Based Learning dalam Pembelajaran PAI di Madrasah Aliyah Publikasi 2010-2025” - Sumiati Gusri; Martin Kustati; Bashori (Advances In Education Journal, 2025)
The development of Problem-Based Learning (PBL) in Islamic Religious Education (PAI) at Madrasah Aliyah (MA) faces challenges due to limited mapping of thematic trends and research gaps, leaving educators and researchers uncertain about its evolution. This study aims to systematically analyze the evolution of PBL concepts in PAI, identify key thematic clusters, and reveal emerging research trends. Data were collected from 2010 to 2025 through indexed journal publications, focusing on titles, abstracts, and keywords. Keyword mapping was conducted using VOSviewer to visualize relationships among research themes. The results indicate a clear shift from traditional cognitive-focused PBL to approaches integrating digital learning, critical religious literacy, character education, and collaborative problem-solving. Key clusters include “PBL,” “PAI,” “critical thinking,” “student engagement,” and “digital learning.” The novelty of this study lies in providing the first comprehensive bibliometric keyword mapping of PBL in PAI at the MA level, offering insights for curriculum development, pedagogical innovation, and future research directions in Islamic education.